PENGARUH CITRA MEREK, HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA PERUSAHAAN PROPERTY DI KOTA BATAM - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This study aims to determine the influence of brand image, price and quality of service to customer loyalty in property companies in Batam. This study uses questionnaires distributed to customers of property companies in Batam City by distributing questionnaires 124 respondents. This study uses the level of individual analysis. The object of research is the customers or customers who have bought a house in the property company in Batam City. This study uses multiple linear regression test which includes the validity, reliability, normality, and r square test. The results showed that the coefficient of determination (R2) has a value of 0.437 which means that the variable of customer loyalty variable can be explained by the variable of brand image, price, and service quality of 43.7%, while the rest is 56.3% influenced by factors not in this study